2006
DOI: 10.1071/ch06141
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Forces of a Supported DOPC Bilayer in the Presence of the General Anaesthetic Halothane — An Atomic Force Microscopy Study

Abstract: In this study atomic force microscopy (AFM) was used to study the effect of halothane on a supported dioleoylphosphatidylcholine (DOPC) bilayer under conditions of high anaesthetic loading. In a previous study we demonstrated that bilayer restructuring occurs as a result of halothane incorporation. Force measurements using AFM indicate an initial decrease in adhesive forces and compressibility between the bilayer and AFM tip, followed by an increase in adhesion properties as a function of incubation time. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Slowly cooling the system back showed that the two higher-temperature transitions at 42-52 and 53-60 • C are reversible and that the bilayer can be restored to its initial thickness [61]. A DOPC bilayer, which exists in a fluid phase at room temperature, when heated shows thickness reduction as well as an increase in surface coverage [62], but no domain formation. Previous studies have established the L β -L α phase transition temperature for DPPC at 41 • C [63].…”
Section: Temperature-dependent Phase Transitionmentioning
confidence: 99%
“…Slowly cooling the system back showed that the two higher-temperature transitions at 42-52 and 53-60 • C are reversible and that the bilayer can be restored to its initial thickness [61]. A DOPC bilayer, which exists in a fluid phase at room temperature, when heated shows thickness reduction as well as an increase in surface coverage [62], but no domain formation. Previous studies have established the L β -L α phase transition temperature for DPPC at 41 • C [63].…”
Section: Temperature-dependent Phase Transitionmentioning
confidence: 99%